Effect of Prolactin Hormone on Reproductive activity and some physiological parameters of Rabbits - Yaseen, Rand T.; Mohammed, Amira K.; Al-Ghetaa, Hassan F. Kashef (The Iraqi Journal of Veterinary Medicine, 2012)
The objective of the present study was to determine the influence of prolactin hormone on reproductive activity of female rabbit. Study was conducted on the laboratory animal house and it depended on fifteen mature rabbit does and one mature buck housed on a special cage separately. The females were divided randomly into two groups; the first group is Control group: Female of this group (n=7) were administrated 2 ml of normal saline orally /day. second group is treated group: Females of this group (n=8) were received orally 5 mg of Parlodil® (Bromocriptine) daily for 5 consecutive days then stopped one week and repeated in the same schedule. All animals were clinically observed for detect any drug reaction and signs of sexual behavior. Vaginal smears were taken to determine any changing. The results of the study revealed: Emerge of estrus at the third dose of treatment in five does (First course) and conceive with a male and three of them had been pregnant these pregnant does were aborted in post treatment period (after the end of the second course of treatment). The results of vaginal smears showed significant increase (P<0.05) in percentage of intermediate epithelial cells in treated group in comparison with control group simultaneously with significant decrease in superficial component. While the parabasal cells not showed differences between groups, but there was a significant decline in percentage via treating period in comparison with other study periods in treated group female. The treatment does not affect significantly on the blood parameters involved in this study except white blood cells count which decreased significantly in treated group during post treatment period while prolactin hormone concentration in treated group sera was dropped significantly immediate with starting the administration of parlodil. In conclusion, the Prolactin hormone have a role in maintenance of corpus luteum in rabbits and the treatment with dopamine agonist (Bromocriptine) leads to loses of the pregnancy. The variation of the epithelial component of the vaginal smear has no value in detection of sexual activity for the rabbits.